Video-measured fullness cues in baby-led weaned and traditionally spoon-fed infants and subsequent intake - Alice M. Cox; Anne-Louise M. Heath; Jillian J. Haszard; Lisa A. Te Morenga; Kathryn L. Beck; Cathryn A. Conlon; Lisa Daniels; Ioanna Katiforis; Madeleine Rowan; Neve H. McLean; Bailey R. Bruckner; Rachael W. Taylor (Appetite, 2026)

Dental microwear of Neogene cercopithecoids from the Turkana Basin, Kenya - Leah K. Fehringer; Catherine C. Beck; Louise N. Leakey; Patricia Princehouse; John Rowan; Gabrielle A. Russo; Mark F. Teaford; Kevin T. Uno; Peter S. Ungar (Journal of Human Evolution, 2025)

Baby food pouches and Baby-Led Weaning: Associations with energy intake, eating behaviour and infant weight status - Alice M. Cox; Rachael W. Taylor; Jillian J. Haszard; Kathryn L. Beck; Pamela R. von Hurst; Cathryn A. Conlon; Lisa A. Te Morenga; Lisa Daniels; Jenny McArthur; Rebecca Paul; Neve H. McLean; Emily A. Jones; et al. (Appetite, 2024)

Candidate master microRNA regulator of arsenic-induced pancreatic beta cell impairment revealed by multi-omics analysis - Jenna E. Todero; Kieran Koch-Laskowski; Qing Shi; Matt Kanke; Yu-Han Hung; Rowan Beck; Miroslav Styblo; Praveen Sethupathy (Archives of Toxicology, 2022)
Arsenic is a pervasive environmental toxin that is listed as the top priority for investigation by the Agency for Toxic Substance and Disease Registry. While chronic exposure to arsenic is associated with type 2 diabetes (T2D), the underlying mechanisms are largely unknown. We have recently demonstrated that arsenic treatment of INS-1 832/13 pancreatic beta cells impairs glucose-stimulated insulin secretion (GSIS), a T2D hallmark. We have also shown that arsenic alters the microRNA profile of beta cells. MicroRNAs have a well-established post-transcriptional regulatory role in both normal beta cell function and T2D pathogenesis. We hypothesized that there are microRNA master regulators that shape beta cell gene expression in pathways pertinent to GSIS after exposure to arsenicals. To test this hypothesis, we first treated INS-1 832/13 beta cells with either inorganic arsenic (iAs III ) or monomethylarsenite (MAs III ) and confirmed GSIS impairment. We then performed multi-omic analysis using chromatin run-on sequencing, RNA-sequencing, and small RNA-sequencing to define profiles of transcription, gene expression, and microRNAs, respectively. Integrating across these data sets, we first showed that genes downregulated by iAs III treatment are enriched in insulin secretion and T2D pathways, whereas genes downregulated by MAs III treatment are enriched in cell cycle and critical beta cell maintenance factors. We also defined the genes that are subject primarily to post-transcriptional control in response to arsenicals and demonstrated that miR-29a is the top candidate master regulator of these genes. Our results highlight the importance of microRNAs in arsenical-induced beta cell dysfunction and reveal both shared and unique mechanisms between iAs III and MAs III .

Exposure to inorganic arsenic and its methylated metabolites alters metabolomics profiles in INS-1 832/13 insulinoma cells and isolated pancreatic islets - Yuan-Yuan Li; Christelle Douillet; Madelyn Huang; Rowan Beck; Susan Jenkins Sumner; Miroslav Styblo (Archives of Toxicology, 2020)

Arsenic is more potent than cadmium or manganese in disrupting the INS-1 beta cell microRNA landscape - Rowan Beck; Mohit Chandi; Matt Kanke; Miroslav Stýblo; Praveen Sethupathy (Archives of Toxicology, 2019)